Management of Cattle Dung and Novel Bioelectricity Generation Using Microbial Fuel Cells: An Ingenious Experimental Approach. (31st October 2021) - Kaur, Gagandeep; Brar, Yadwinder Singh; Kaur, Jaspreet; Gupta, Akhil; Sharma, Kamal Kant; Chohan, Jasgurpreet Singh; Kumar, Raman; Sharma, Shubham; Chattopadhyaya, Somnath; Dwivedi, Shashi Prakash; Issakhov, Alibek; Khalilpoor, Nima
Abstract : Microbial fuel cells (MFCs) are the rising modern equipment for the generation of bioelectricity from organic matters. In this study, MFCs in two formats are assembled and concurrently operated for a 30-day period in a batch mode manner. Natural biowaste cattle dung slurry with mediators is used as a substrate persistently for the enhancement of electron transfer rate and additionally for the augmentation of required electrical parameters. Under similar conditions, the MFC setups are experimented with a variety of anode-cathode material combinations, namely carbon-carbon, copper-carbon, and zinc-carbon. The performance of these MFCs during the testing period is evaluated independently and compared by plotting polarization data generated by them. It is revealed that maximum current and power densities are achieved from all these MFCs and the best attained values are 1858 mA/m 2 and 1465 mW/m 2, respectively, for the novel single-chamber zinc-carbon electrode MFC. The corresponding findings present that the MFC with zinc-carbon electrodes has the better power density than other MFCs. Being conductive and higher standard potential metal electrodes have improved the capability to act in place of carbon family electrodes for MFC-based power applications. Although the MFC power generation is low, but modifications in configurations, electrodes, microbe-rich biowaste, mediators, and power management may enhance the power output to a significant level for commercialization of this technology. The unique feature of this research is to explore the pertinent use of conductive metal electrodes to enhance the power generation capability of MFCs through biowaste as an alternative power source for small applications. The novelty of this research is presented through usage of conductive metal electrodes for the performance analysis of MFCs.